PEMBERDAYAAN PEREMPUAN MELALUI PELATIHAN KECANTIKAN TATA RIAS WAJAH - Nasya Octavia Fauziah; Arin Khairunnisa (Yayasan Nusantara Hasana Berdikari, 2023)
Make-up, or what we often know, namely make-up, is done by women or women as a form of business to beautify themselves in order to make their appearance more attractive. The purpose of this cosmetology beauty training activity is so that women or women, especially housewives, can improve facial cosmetology techniques. This training is carried out by presenting tutors and models to make up as examples for the trainees. After that, the participants practiced the makeup on the models that had been prepared. The enthusiasm of the training participants was evident from the many questions asked about cosmetics that were good for various types of facial skin. Most of the participants already knew some of the makeup techniques.